Comparison of the effects of zinc oxide and zinc aspartic acid chelate on the performance of weaning pigs - Sarbani Biswas; De Xin Dang; In Ho Kim (Journal of Animal Science and Technology, 2024)
In this research, the growth efficiency, nutritional utilization, fecal microbial levels, and fecal score of weaned pigs were evaluated using therapeutic zinc oxide (ZnO) and zinc aspartic acid chelate (Zn-Asp). In a 42-day feeding trial, 60 weaned pigs ([Yorkshire × Landrace] × Duroc) were arbitrarily allotted (age: 21 days; 7.01 ± 0.65 kg preliminary body weight) to 3 different treatment groups with 5 repetitions (2 male and 2 female piglets) in each pen. The trial had 2 different phases, including 1–21 days as phase 1, and 22–42 days as phase 2. The nutritional treatments were: basal diet as control (CON), basal diet incorporated with 3,000 ppm ZnO as TRT1, and basal diet incorporated with 750 ppm Zn-Asp as TRT2. In comparison to the CON group, the pigs in the TRT1 and TRT2 groups had greater (p < 0.05) body weight on day 42; an average daily gain, and an average daily feed intake on days 22–42. Furthermore, during days 1-42, the average daily gain in the treatment groups trended higher (p < 0.05) than in the CON group. Additionally, the fecal score decreased (p < 0.05) at week 6, the lactic acid bacteria count tended to increase (p < 0.05), and coliform bacteria presented a trend in reduction (p < 0.05) in the TRT1 and TRT2 groups compared to the CON group. However, there was no difference in nutrient utilization (p > 0.05) among the dietary treatments. Briefly, the therapeutic ZnO and Zn-Asp nutritional approaches could decrease fecal score and coliform bacteria, increase lactic acid bacteria, and improve growth efficiency; moreover, Zn-Asp (750 ppm) can perform a comparable role to therapeutic ZnO (3,000 ppm). So we can use Zn-Asp (750 ppm) instead of therapeutic ZnO (3,000 ppm) for the better performance of weaning pigs and the reduction of environmental pollution, as therapeutic ZnO is responsible for environmental pollution.